Parent training for disruptive behavior symptoms in attention deficit hyperactivity disorder: a randomized clinical trial - Paiva, Gabrielle Chequer de Castro; de Paula, Jonas Jardim; Costa, Danielle de Souza; Alvim-Soares, Antônio; Santos, Daniel Augusto Ferreira e; Jales, Julia Silva; Romano-Silva, Marco Aurélio; Miranda, Débora Marques de (Frontiers in Psychology, 2024)
Background Attention-Deficit/Hyperactivity Disorder (ADHD) affects 5% of children and 2.5% of adults worldwide. Comorbidities are frequent, and Oppositional Defiant Disorder (ODD) reaches 50%. Family environment is crucial for the severity of behaviors and for prognosis. In middle-income countries, access to treatment is challenging, with more untreated children than those under treatment. Face-to-face behavioral parent training (PT) is a well-established intervention to improve child behavior and parenting. Method A clinical trial was designed to compare PT-online and face-to-face effects to a waiting list group. Outcomes were the ADHD and ODD symptoms, parental stress and styles, and quality of life. Families were allocated into three groups: standard treatment (ST), ST + PT online, and ST + Face-to-Face PT. We used repeated measures ANOVA for pre × post treatment analysis corrected for multiple comparisons. Results and discussion Parent training was effective in reducing symptoms of ADHD (p = 0.030) and ODD (p = 0.026) irrespective of modality (p = 1.000). The combination of ST and PT was also associated with better quality of life in the physical domain for patients (p = 0.009) and their parents (p = 0.050). In addition to preliminary data, online intervention seems effective for parenting and improving social acceptance of children. The potential to reach many by an online strategy with a self-directed platform may imply effectiveness with a low cost for public health to support parents’ symptoms management.